BUDAYA ETIS MEMEDIASI HUBUNGAN ANTARA TEKANAN ANGGARAN WAKTU DAN KUALITAS AUDIT (Studi Empiris pada Auditor KAP di Kota Semarang) - Latifa, Devi Anisa; Ghozali, Imam (Diponegoro Journal of Accounting, 2015)
The purpose of this study is to analyze how time budget pressure affect audit quality by ethical culture and how ethical culture mediate an indirect effect of time budget pressure on audit quality.In this study, the form of primary data collected by using questionnaire that shared for auditor in Semarang. Fifty samples are used in this study. Data analyzed with the quality data test, classic assumption test, and the examination of the hypothesis using model of multiple linear regression, path analysis.The results show that time budget pressure does have negative impact to the audit quality and also ethical culture. The ethical culture is found to have positive impact to the audit quality. From this results can be concluded that the ethical culture does not mediate in indirect effect of time budget pressure on audit quality.